Synergy of Digitalization and Firm Size to Optimize Financial Performance: An Empirical Study of Three Asean Countries - Abdul Ghofar; Areta Widya Kusumadewi; Rika Nur Widiastutik (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This study aims to analyze the effect of firm size and digitalization on financial performance. It also examines the moderating role of digitalization in the relationship between firm size and financial performance. Methodology/approach: A quantitative approach is employed in this study, grounded in established theory to develop a conceptual framework and hypotheses. The analysis is conducted using data and quantitative statistical techniques to test the relationships between variables. Findings: The results reveal that firm size and digitalization do not consistently have a positive impact on financial performance. In Indonesia and Singapore, firm size enhances financial performance, but not in Malaysia. Conversely, digitalization improves financial performance in Malaysia but fails to do so in Indonesia and Singapore. Furthermore, in Malaysia, digitalization weakens the relationship between firm size and financial performance, whereas no moderating effect is found in Indonesia and Singapore. Practical implications: The findings highlight the need for context-specific digitalization strategies. In Malaysia, continued government support for digitalization is essential. In contrast, companies in Indonesia and Singapore should balance digital investment with efficiency and competitiveness strategies. Originality/value: This study introduces digitalization as a moderating variable to clarify previous inconsistencies regarding the impact of firm size on financial performance, considering differences between developing and developed countries.